Activation of the aryl hydrocarbon receptor decreases rifampicin-induced CYP3A4 expression in primary human hepatocytes and HepaRG. (5th August 2017) - Rasmussen, Martin Krøyer; Daujat-Chavanieu, Martine; Gerbal-Chaloin, Sabine
Graphical abstract: Highlights: Cross-talk between receptors regulating cytochrome p450 expression is well known. In HepaRG, AhR ligands decreases basic and rifampicin-induced CYP3A4 mRNA expression. In human hepatocytes, AhR ligands decrease the rifampicin-induced CYP3A4 expression. AhR knock-down increases basic CYP3A4 mRNA expression in human primary hepatocytes. Cross-talk between AhR and PXR are suggested. Abstract: The role of the cross-talk between nuclear receptors in the regulation of Cytochrome P450 expression in the liver is well-documented. Most studies have focused on the cross-talk between the pregnane X receptor (PXR) and other receptors, such as the constitutive androstane receptor. However, cross-talk between PXRs and aryl hydrocarbon receptors (AhRs) has also been suggested, but reports regarding this cross-talk are conflicting. In the present study, we treated HepaRG and primary human hepatocytes (PHHs) with both a strong (TCDD) and weak (3-methylindole; 3MI) AhR activator to investigate their impact on PXR-regulated expression of CYP3A4. Moreover, we investigated the effect of co-activation of PXR, using rifampicin, and AhR, using TCDD and 3MI, on the regulation of CYP3A4 induction. We also investigated whether knockdown of AhR using siRNA affected the basal expression of PXR and CYP3A4 and induction of CYP3A4 by rifampicin, TCDD and 3MI. The results showed that the treatment of HepaRG cells, but not of PHHs, with AhR activators decreased mRNA expression of CYP3A4 and PXR . Moreover, in both HepaRG and PHHs, AhR activation decreased rifampicin-induced expression of CYP3A4 mRNA. Knock-down of AhR in PHHs increased both basal and rifampicin-induced expression of CYP3A4 mRNA. In conclusion, the presented results suggested that the cross-talk between PXR and AhR plays a role in the regulation of CYP3A4 gene expression.